On the Non-linear Damping of Mechanical Oscillators in Flows of 4He - Schmoranzer, D.; Jackson, M.J.; Luzuriaga, J. (Springer Nature, 2014)
Fil: Luzuriaga, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina